An In Vivo Study on Intoxicating Effects of Nerium oleander Water Based Extract on Multiorgans of Wistar Rat. (23rd April 2018) - Abbasi, Muddasir Hassan; Fatima, Sana; Khawar, Muhammad Babar; Jahan, Shah; Sheikh, Nadeem
Abstract : This study was aimed to find histological changes in the extrahepatic organs, hepatic iron deposition, and gene expression of some iron regulatory proteins in rats after sterile muscle abscess during the acute intoxication of Nerium oleander leaves decoction. 10 ml/kg of the leaves extract was injected intramuscularly in Wistar rats (200–225 g, n = 4 ). Control animals received saline injection of matched volume. Animals were anesthetized and sacrificed after 3, 6, 12, and 24 h after administration of decoction. Lungs, kidney, spleen, and liver were extracted and processed for histopathological examination while portion of liver tissue was proceeded for iron regulatory gene expression quantification. Sections of all studied organs were found with signs of cellular dysfunction with infiltration of variety of leucocytes. In the lungs section at 3 h time point mononuclear cell infiltrates were observed while in alveolar tissue at 24 h time point dilation and even collapse in some of the alveoli were evident. In kidney sections distortion of renal tubules and epithelial cells with shrinkage of glomeruli was noted at all studied time points. In the splenic section of 12 h time point, degeneration, depopulation, and shrinkage of white pulp have been noted. Distension of the red pulp along with activation of splenic follicles was evident after 24 h onset of APR. Significant changes in the expression of acute phase cytokine and iron regulatory genes were noted. IL-6 and Hepc gene expression were strongly upregulated up to 12 h whereby Tf gene expression showed an early upregulation at 3 h time point followed by downregulation on later points while Hjv gene expression showed an overall downregulation at all study time points compared to control. It is concluded that inherent toxins present in the N. oleander can induce acute phase response and cause severe histological changes in the organs and marked changes in the regulation of iron regulatory proteins thus cannot be practiced routinely.